Analysis Of Non Value Added Activity On Ship Production Process Approach Concept Of Value Stream Mapping Case Study At PT. Dumas Tanjung Perak Shipyard Surabaya - An Apriyani Tebiary; I Ketut Suastika; Buana Ma'ruf (Wave: Jurnal Ilmiah Teknologi Maritim, 2017)
Competition of shipyard industry market in this globalization era encourages companies to realize the importance of improving the effectiveness and efficiency so that, able to compete in terms of quality, cost and on time delivery. Production effectiveness is one effort that must be achieved by a shipbuilding industry to survive amid the competition in seizing market share. Production effectiveness is done with the aim of producing economically, continuously and on time to the customer, so that the company's survival can be guaranteed. This study aims to identify the activities that are classified as waste in the process of ship building at PT. Dumas Tanjung Perak Shipyard Surabaya so as to minimize production time in shipyard industry. The results showed the effectiveness of PT. DUMAS currently reaches 84.96%. In the process of improvement with the application of value stream mapping effectiveness value reached 92%. The conclusion of this research is a value stream mapping method can be applied measuring instrument and can describe the flow of production process in shipyard so that can explain in detail activity that give value added or non value added activity.